Procedimentos aplicáveis na definição de medidas para a manutenção de pavimentos urbanos com revestimentos asfálticos - Scaranto, Marcelo (2007)
This work presents evaluation procedures for urban pavements that will generate maintenance measures adjusted to the situation in Brazil. Firstly, the main techniques for pavement evaluation in use today are presented. In a second moment, having as goal the establishment of draining, traffic and surface conditions, a proposal evaluation for urban pavements with asphalt covering is developed. Based on this proposal, it is elaborated a methodology that enables to diagnose actual maintenance needs (AMN) for roads under evaluation. The diagnosis is established through the analysis of serviceability values (PSI, PSIQI, PSR and PSIIDS), concepts-result provided by decision trees and also through questionings proposed in the present study. Having obtained the diagnosis, and bearing in mind the road user s serviceability expectation, a suggestion leading to maintenance solutions that aim at recovering the pavement in stages is presented. Simultaneously, urban pavement sections were selected for practical applications of the evaluation procedures, diagnosis and definition of maintenance solutions. These practical applications, which were put into effect in the towns of Erechim and Santa Maria, enabled the establishment of procedures improvements in order to obtain important diagnosis information. Finally, it is safe to say that the criteria proposed here have shown themselves adequate, for they have provided coherent results with the situation presented by the pavements analyzed